THE EFFECT OF SOCIAL MEDIA E-MARKETING TOWARDS CONSUMERS SHOPPING BEHAVIOR - Arius Krypton Onarelly; Naldo Tantuah; Hardika Widi Satria (Program Pendidikan Vokasi Universitas Indonesia, 2018)
Abstract: As the numbers of Internet users increase, the trend of online transactions also increase. E- marketing is one of a selling strategy using social media such as Facebook, Instagram, Twitter, Whatsapp, BBM and LinkedIn. The purpose of this study was to analyze the simultaneous and partial effect of E-Marketing to the shopping behavior of respondents. Data were obtained from questionnaires given to 100 student respondents of Indonesian vocational education. The analytical method used in this research is the t test and F test using SPSS 17. Based on results of the study it is found that three factors affected shopping behavior of these respondents through their online transaction via social media, namely accessibility, currency and interactivity. All e-marketing variables influenced the behavior of consumers. However, there are also some e-marketing variables affecting shopping behavior of respondents in different factors. From the cultural factor, shopping behavior is influenced by the accessibility and currency variables, while an effected variable linked to personal factors is accessibility alone. For psychological factors, the only effecting variable is interactivity. But overall e-marketing variables affected the shopping behavior of respondents.Keywords: Consumer behavior, E-marketing, Online shop, Social media, Shopping, Qualification